THE INFLUENCE OF LEVERAGE AND CAPITAL INTENSITY ON ACCOUNTING CONSERVATISM - Rifka Annisa Effendi; Made Gede Wirakusuma (Adisam Publisher, 2025)
This study aims to examine the influence of leverage and capital intensity on accounting conservatism in companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Accounting conservatism is regarded as a prudence principle in financial reporting, which is essential for minimizing the risk of overly optimistic reporting—particularly for firms with complex financing structures. Utilizing the Efficient Contracting Theory, this research focuses on how leverage, which reflects the proportion of debt financing, and capital intensity, which indicates the level of fixed asset investment, may influence the degree of accounting conservatism. The sample consists of 417 companies selected through purposive sampling, resulting in a total of 2,085 annual observations. The analytical model employed is multiple linear regression using the Fixed Effect Model (FEM), along with classical assumption tests and partial hypothesis testing. The results indicate that leverage has no significant influence on accounting conservatism, while capital intensity has a significant positive influence.